Selection of railway line segments that allow occupation by more trains based on simulation - Bulíček, Josef; Bažant, Michael (CAL-TEK SRL, 2020)
The paper is focused on research of railway infrastructure capacity assessment by computer simulation method. Specific goal of this paper is to discuss tools and possibilities for assessment, which segments of railway line can be divided into spatial segments for improving of capacity. This division can be done by using line blocks or more advanced systems, so called moving blocks, like ETCS L3 or interlocking and control systems based on on-line location of trains and controlling the gap between trains. The presumption is that equipment of a line segment between stations with such system costs considerable funds. Proposed method in this paper can help how to identify which segments have priority to be equipped or not. Simulation and transport technology points of view are combined in the paper.
Výběr mezistaničních úseků, na kterých bude umožněno obsazení více vlaky, s využitím simulace
Keywords: capacity; model; railway; simulation; kapacita; model; železnice; simulace